2013
DOI: 10.2174/1871525711311010006
|View full text |Cite
|
Sign up to set email alerts
|

Hibiscus Sabdariffa Linnaeus (Malvaceae), Curcumin and Resveratrol as Alternative Medicinal Agents Against Metabolic Syndrome

Abstract: Metabolic syndrome (MS) is an obesity-associated collection of disorders, each of which contributes to cardiovascular risk. For patients with MS, it is difficult to follow a diet/exercise regime that would improve their symptoms. Therefore, the investigation of agents that may deal with its more serious aspects is an important medical field for research. Numerous experimental studies have confirmed the important role of medicinal plants or their active components in the prevention and treatment, and in lowerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 0 publications
3
53
0
1
Order By: Relevance
“…Similar effects on lipids have been found in another study without significant effect on blood glucose with 2 g of Turmeric powder taken for 8 weeks. 38 When given alone, Black seeds reduced cholesterol and triglycerides but had no effect on LDL-cholesterol and HDLcholesterol as compared to baseline data. Previous studies also found insignificant increase in HDL-cholesterol when Black seeds powder was given for 2 month, though significant improvement was observed in 6 months.…”
Section: Discussionmentioning
confidence: 89%
“…Similar effects on lipids have been found in another study without significant effect on blood glucose with 2 g of Turmeric powder taken for 8 weeks. 38 When given alone, Black seeds reduced cholesterol and triglycerides but had no effect on LDL-cholesterol and HDLcholesterol as compared to baseline data. Previous studies also found insignificant increase in HDL-cholesterol when Black seeds powder was given for 2 month, though significant improvement was observed in 6 months.…”
Section: Discussionmentioning
confidence: 89%
“…The hypoglycaemic effect of curcumin was first reported in 1972 and recently gained scientific attention as a potential therapeutic agent in experimental diabetes and for the treatment of the various complications in diabetic patients (Torres et al, 2013). It is also relatively inexpensive and safe (Chuengsamarn et al, 2012;Goel et al, 2008;Shehzad et al, 2011).…”
Section: Effect Of Curcumin On Diabetesmentioning
confidence: 99%
“…Development of type 2 diabetes may involve deregulation of adiponectin secretion. Recent studies revealed that curcumin stimulated human adipocyte differentiation [7] and suppressed macrophage accumulation or activation in adipose tissue [61] by regulating adiponectin secretion [29, 62]. The mechanism may be due to suppression of NF- κ B activation [63], which reduces TNF- α and nitric oxide (NO) and inhibits the release of monocyte chemotactic protein-1 (MCP-1) from 3T3-L1 adipocytes [61].…”
Section: Curcumin and Adipose Tissue Dysfunctionmentioning
confidence: 99%
“…The most active component of turmeric, curcumin, has caught scientific attention as a potential therapeutic agent in experimental diabetes and for the treatment of the complications of diabetes patients [7], primarily because it is effective in reducing glycemia and hyperlipidemia in rodent models and is relatively inexpensive and safe [810]. The structure of curcumin (Figure 1(c)), shown to be a diferuloylmethane, was resolved by Lampe and Milobedeska in 1910 [11].…”
Section: Introductionmentioning
confidence: 99%